Local flavour, film fantasies and shifting selections: Finnish sex magazines, 1972–1973 - Paasonen Susanna; Saarenmaa Laura (United Kingdom, 2025)
The years 1972–1973 marked a period of transformation towards both hardcore print content and centralized production within the Finnish sex press. In a national context where the distribution and accessibility of screen porn was strictly regulated, periodicals remained the key platform for sexual content, and the leading ones were published by mainstream media houses also trading in women’s magazines and comics. Through examination of 15 sex magazine titles published in Finland during this period, this article inquires after the visibility and invisibility of porn films within them, contextualizes the print market in terms of publishing economy and governmental regulation and attends to the methodological challenges involved in porn historiography.